The gender prosecution at the Ibero-American Judicial Summit - Lousada Arochena, José Fernando (2020)
This paper will analyze the underlying problem of gender prosecution: the harmful use of gender stereotypes. By its own definition, prosecuting involves evaluating the evidence practiced in a trial to identify facts to which a specific legal consequence provided by law is attached. In this sense, when this judicial syllogism introduces a gender prejudice, it distorts the assessment of evidence, fails to identify the facts and distorts the correct application of legal norms.